1998
DOI: 10.1111/j.1572-0241.1998.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Bowel Preparations for Colonoscopy: Sodium Picosulphate With Magnesium Citrate Versus Sulphate-Free Polyethylene Glycol Lavage Solution

Abstract: Colonic preparation with SPS-Mg is better tolerated, associated with significantly fewer side effects, and results in higher quality bowel cleansing than preparation with PEG-EL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 19 publications
2
28
0
Order By: Relevance
“…Of all the problems that may be caused by volume load (nausea, vomiting, bloating, pain) only nausea and bloating occurred less frequently a er PMC. e same conclusion was drawn in the trial of Regev et al [11]. Better tolerance of PMC may be explained by properties of the compound itself.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Of all the problems that may be caused by volume load (nausea, vomiting, bloating, pain) only nausea and bloating occurred less frequently a er PMC. e same conclusion was drawn in the trial of Regev et al [11]. Better tolerance of PMC may be explained by properties of the compound itself.…”
Section: Discussionsupporting
confidence: 70%
“…However, the tolerance of PMC was better and with fewer side e ects such as nausea, vomiting or abdominal pain [9,10]. In a randomised trial [11] Regev et al found PMC to be associated with better bowel cleansing and patient acceptability than PEG. However, the authors compared various doses and duration of the preparation (3L of PEG in the a ernoon and 3 sachets of PMC from the morning the day before the colonoscopy).…”
Section: Discussionmentioning
confidence: 99%
“…Low‐volume SPMC has been shown to have greater tolerability and equal or greater efficacy compared with sodium phosphate,22 2 L PEG and bisacodyl,5, 6 2 L PEG with ascorbic acid,23 3 L of sulfate‐free PEG,24 and 4 L PEG preparations 25. Non‐inferiority of SPMC to PEG has also recently been shown in a meta‐analysis 26.…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, it is a good colon cleanser and usually easier to ingest. 7 MC-SP complex acts locally in the colon as a combination of a stimulant laxative to increase frequency and strength of peristaltsis (sodium picosulfate component) and as an osmotic laxative to retain fluid in the colon (magnesium citrate component). 2 Compared with PEG and NaP solutions, it has similar bowel cleaning efficacy but the patient's compliance has been reported to be better than with PEG and NaP.…”
Section: Discussionmentioning
confidence: 99%